Factors underlying inadequate parents' awareness regarding pediatrics immunization: findings of cross-sectional study in Mosul-Iraq - Al-lela, Omer QB; Bahari, Mohd B; Salih, Muhannad RM; Al-abbassi, Mustafa G; Elkalmi, Ramadan Mohamed Mahmod; Jamshed, Shazia Qasim (BioMed Central Ltd, 2014)
Background Since last 100 years, immunization rate is one of the best public health outcome and service indicators. However, the immunization system is still imperfect; there are many countries that still have unvaccinated children. Parental decisions regarding immunization are very important to improve immunization rate. The aim of this study is to evaluate the association between parental knowledge-practice (KP) regarding immunization with family and immunization providers’ factors.